2012
DOI: 10.1093/jxb/err452
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis mutant, fy-1, has an ABA-insensitive germination phenotype

Abstract: Arabidopsis FY, a homologue of the yeast RNA 3' processing factor Pfs2p, regulates the autonomous floral transition pathway through its interaction with FCA, an RNA binding protein. It is demonstrated here that FY also influences seed dormancy. Freshly-harvested seed of the Arabidopsis fy-1 mutant germinated readily in the absence of stratification or after-ripening. Furthermore, the fy-1 mutant showed less ABA sensitivity compared with the wild type, Ler, under identical conditions. Freshly-harvested seed of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 35 publications
3
23
0
Order By: Relevance
“…3 and Supplementary Fig. S2; Jiang et al ., 2012). ABI5 and/or other ABFs could distinctly promote the expression of FLC (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…3 and Supplementary Fig. S2; Jiang et al ., 2012). ABI5 and/or other ABFs could distinctly promote the expression of FLC (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…2), and SnRK2.3 (Finkelstein and Somerville, 1990;Söderman et al, 2000;Carles et al, 2002;Fujii et al, 2007;Tran et al, 2007;Moes et al, 2008;Li et al, 2011;Jiang et al, 2012;Du et al, 2013;Kim et al, 2013), in the wild type, myb96-ox, and myb96-1, in the absence of ABA. In seeds, many genes were differentially expressed in myb96-ox and myb96-1, but MYB96 regulation of ABI4 was most likely relevant (Fig.…”
Section: Abi4 Is Up-regulated In Myb96-oxmentioning
confidence: 99%
“…FY is the Arabidopsis homolog of the yeast RNA 39 processing factor Pfs2p (Simpson et al, 2003). A previous study demonstrated that the fy-1 mutant in Landsberg erecta background has weak seed dormancy (Jiang et al, 2012). To check if the function of FY in seed dormancy control is independent of genetic background, we Figure 1.…”
Section: Mutants Of Rna 39 Processing Factors Display Weak Seed Dormamentioning
confidence: 99%